The Asia‐Pacific iSchools. Issue 4 (April 2016) - Oh, Sam
Abstract : EDITOR'S SUMMARY The Asia‐Pacific iSchool regional chapter, initiated in 2014, consists of nine of the 11 iSchools across Australia, China, Japan, Korea and Singapore. The curricula and research areas of the iSchools in the region vary widely. Sungkyunkwan University in Korea offers a general B.A. in library and information science and a more technical B.S. in data science, as well as master's and doctoral programs geared to research. Other schools in the chapter offer programs ranging from publishing and e‐commerce to software engineering and information systems. The vibrant young chapter is working creatively on mutual support, outreach and funding. Member schools agree on a number of agenda items to strengthen the chapter, but, without a shared body for collaborative work, most maintain stronger partnerships with institutions in Europe and North America.